Analysis of Opportunities and Threats in the Buffalo Meat Import Trade: A Case Study of Trade Between Indonesia And India - Intan Apprinella; Daspar Daspar (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study examines the opportunities and threats associated with buffalo meat import trade between Indonesia and India during the period 2020 to 2025. The research employs an empirical quantitative approach using descriptive analysis based on secondary data obtained from official statistical publications, government reports, market records, and trade related documents. The analysis focuses on import growth, supply availability, market expansion potential, import dependency, domestic livestock competitiveness, and strategic trade risks. The findings indicate that buffalo meat imports have contributed to strengthening national meat supply capacity and improving market accessibility through the utilization of India's comparative advantage in buffalo production. However, increasing reliance on a dominant supplier has generated concerns regarding market concentration, food security vulnerability, and reduced competitiveness of domestic livestock producers. The study also identifies significant external risks related to animal disease outbreaks, biosecurity challenges, logistics disruptions, export restrictions, and sustainability transitions within the global livestock industry. The results suggest that while buffalo meat imports offer economic and supply related benefits, long term resilience requires balanced trade governance, supplier diversification, strengthened sanitary controls, and sustained investment in domestic livestock development to ensure food security and agricultural sustainability.